2014
DOI: 10.1111/dom.12386
|View full text |Cite
|
Sign up to set email alerts
|

Using real‐world data to evaluate the association of incretin‐based therapies with risk of acute pancreatitis: a meta‐analysis of 1 324 515 patients from observational studies

Abstract: The present meta-analysis of real-world data does not suggest that IBT is associated with AP. Although we should continue to remain vigilant, IBTs should be regarded as reasonable options to consider adding to the regimen of a patient with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 47 publications
8
39
0
6
Order By: Relevance
“…At present, several meta-analyses have been carried out with regards to the safety of incretin-based therapy [3549]. It is reported that incretin-based drugs are associated with increased risk of cardiovascular events, acute pancreatitis and several types of neoplasm [3549].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, several meta-analyses have been carried out with regards to the safety of incretin-based therapy [3549]. It is reported that incretin-based drugs are associated with increased risk of cardiovascular events, acute pancreatitis and several types of neoplasm [3549].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that incretin-based drugs are associated with increased risk of cardiovascular events, acute pancreatitis and several types of neoplasm [3549]. However, some meta-analyses had only focused on evaluation of a single drug classified within the incretin drug category [36, 38, 39, 45, 48].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the analysis of three retrospective cohort studies and two case-control studies (total n = 320,289) did not show an increased risk of pancreatitis with the administration of exenatide or sitagliptin [83]. Likewise, another recent meta-analysis of nine observational studies (n = 1,324,515 patients and 5,195 cases of acute pancreatitis) found no significant association between incretin-based treatment and acute pancreatitis (OR: 1.03, 95% CI: 0.87-1.20) [84]. Furthermore, FDA and European Medicines Agency (EMA) recently reevaluated more than 250 toxicology studies conducted in nearly 18,000 healthy animals and more than 200 trials involving approximately 28,000 patients taking incretin-based drugs.…”
Section: Pancreasmentioning
confidence: 94%
“…Meta-analyses have shown no significant increase in acute pancreatitis with GLP-1RA treatment in patients with T2DM 179,274,275 . In addition, results from cardiovascular safety trials have not shown a significant increase in pancreatitis with GLP-1RAs 276 .…”
Section: Safety and Adverse Effectsmentioning
confidence: 99%